FILSAFAT PENDIDIKAN MERUPAKAN JIWA DARI JURUSAN PENDIDIKAN GURU SEKOLAH DASAR (Educational Philosophy as the Soul of the Department of Primary School Teacher Education) - Jaino, Jaino (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2010)
Education is one of human beings’ life aspects, because a human is the only one who can get education. Therefore education needs a philosophy, on account of the fact that educational problems relate to educational realization. In education realization, it will appear broader and more complex problems that cannot be limited by experiences and facts, and it cannot also be reached by knowledge. Educational philosophy does not relate to facts only, but it also relates to goodness and badness, forms of human’s life, and human’s perfect social life. It means that education is the implementation of philosophical ideas. In other word, philosophy provides certain basis for educational values, education institutions, and educatioal implementation activities. In this case, the roles of educational philosophy are as pull factors for education itself. In details, educational philosophy becomes the soul and basis for educational implementation. The basis of scientific philosophy relates to ontology, epistemology and the basis of educational antropology science. Formal object of educational science is limited at the scope of human beings only in education situation, so that education in practice can be free of hesitancy. In social situation, a human often behaves unperfectly, only as an individual or social beings behaving collectively. In this case, this behavior is not a matter and can be accepted as long as it is limited at education in macro scope related to structured socio-cultural by certain value systems. Thereby, the basis of educational philosophy must reflect in all activities related to education, both instructional and non-instructional ones. In other words, all teacher’s decisions and activities must be educational. Finally, as a professional worker, a teacher must get sufficient preparations that is based by a set of philosophical assumptions, as the interpretation of appropriate concepts of educational knowledge. Keyword: educational philosophy, pedagogy, and teacher